Horses Drawing : A complete guide to drawing horses and ponies - Mino, Bihira (Independently published., 2023)
this comprehensive guide is designed for beginners who are eager to learn how to draw horses. With easy-to-follow, step-by-step instructions, you will master the art of capturing the beauty and movement of these majestic creatures. From understanding equine anatomy to shading techniques and portraying different angles, this book covers all aspects of drawing horses. Enhance your skills with tips on proportions, eyes, hair, and much more. Unleash your artistic talent and create stunning equine illustrations today!"
3-18 years old.